Utilizing ANP for a Comprehensive Risk Assessment and Mitigation Prioritization of Lithium Battery Energy Storage Systems (LBESS) on Commissioning Service Operation Vessels (CSOV) - Setiawan, Deri; Siswantoro, Nurhadi; Pitana, Trika (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
Integrating Lithium Battery Energy Storage Systems (LBESS) into offshore Commissioning Service Operation Vessels (CSOV) poses significant safety concerns, including fire, explosion, and toxic gas release. The expanding offshore wind industry increases demand for CSOVs equipped with energy storage, making robust risk management essential. This study addresses the critical need to understand and manage LBESS hazards on CSOVs, given the absence of comprehensive international regulations and inherent lithium battery risks like thermal runaway. This study utilizes Risk Assessment data and the Analytic Network Process (ANP) to analyze these hazards and identify optimal mitigation strategies. The research systematically identified six distinct hazards, eighteen main causes, and twenty specific sub-causes through hazard identification (HAZID). A purposive sampling method selected seven qualified practitioners with at least three years of experience in BESS security and risk assessment on CSOVs, including ship construction supervision. Data was collected via a questionnaire using pairwise comparisons and the Saaty scale, processed with Super Decisions software, and combined using Geomean calculations. The ANP analysis shows safety is the top priority for LBESS implementation (63.6%), significantly exceeding environmental (16.3%) and operational (10.2%) factors. Within safety, explosion (39.0%) and fire (25.9%) are the most prevalent hazards, with thermal runaway and battery electrolyte decomposition being key contributors to LBESS failure. For mitigation, the analysis highlights Battery Physical Design and Protection (31.5%), Battery Monitoring and Control Systems (27.9%), and Operational Procedures and Training (15.4%) as crucial. Prioritizing safety is essential for LBESS deployment on CSOVs, with explosion and fire being the most severe threats, and robust engineering and operational protocols are critical mitigation strategies.